USM LGU CHAIRMAN: AIDILFITRI A TIME TO STRENGTHEN FRIENDSHIPS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 4 July 2016 – The Universiti Sains Malaysia (USM) Board of Governors (LGU) Chairman, Tan Sri Datuk Dr. Zulkefli A. Hassan extended Aidil Fitri greetings to the entire USM community, alumni, friends and all Muslims wherever they are.